Optimasi Sintesis Ligan Diheksilditiofosfat (DHDTP) Menggunakan Response Surface Method (RSM) - Hendrati, Diana; Mardhotillah, Yulia; Anggraeni, Anni; Firdaus, M. Lutfi; Wyantuti, Santhy (PendIPA Journal of Science Education, 2022)
Dihexyldithiophosphate (DHDTP) ligand is one of the homologues of dialkyldithiophosphate which is potentially better as an extractant in solvent extraction. The longer the chain in the dialkyldithophosphate compound, ability to dissolve into the organic phase is increasing compared to the shorter chain. The purpose of this study is to synthesize DHDTP ligands and find out the optimum reaction conditions to produce DHDTP ligands with optimal purity using the BoxBehnken (BBD) response surface method (RSM). DHDTP ligands are synthesized from P2S5 by reflux after addition of n-hexanol under a nitrogen gas environment. Ammonium carbonate is added to the reflux to pH 7, then evaporated to remove the solvent. The synthesized DHDTP ligand was then purified by column chromatography with a mobile phase methanol : aquadest (2.5% gradient). DHDTP ligands were examined for purity using a reverse phase HPLC with a mobile phase methanol: aquadest 3: 2. The purity of the best DHDTP synthesis results obtained was 87.34%. The DHDTP ligand formed was characterized to confirm the structure of its ligand compound by using a UV spectrophotometer in which the synthesis product showed maximum absorption at a wavelength of 212 nm and mass spectroscopy ES- with m / z 297.1687.